SERVICE CENTER HIERARCHY IN GORONTALO: EMPIRICAL ANALYSIS THROUGH SCALOGRAM AND CENTRALITY - Kalzum R. Jumiyanti; Joachimu Stanley Machimu; Dewi Walahe (Journal of Applied Economics in Developing Countries, 2026)
Regional disparities in service infrastructure persist across Indonesia despite spatial planning efforts. This study addresses the critical gap between normative planning (RTRW 2012) and empirical service center hierarchy in Gorontalo Regency. Using an integrated approach combining Guttman scalogram analysis and Marshall centrality index—a methodological innovation in regional analysis—we identified five hierarchical levels of service centers based on facility distribution across 19 sub-districts. The key finding reveals a serious asynchronization between planned hierarchy (RTRW) and empirical reality: while Tibawa is designated as the regional activity center (PKW), scalogram analysis demonstrates that Limboto and Telaga represent the functionally dominant centers with significantly higher service capacity and facility diversity. Conversely, several peripheral zones designated as PPL (environmental service centers) show higher potential than planned estimates. These findings demonstrate that spatial planning in Gorontalo Regency has not effectively aligned with actual economic and infrastructure development patterns. We recommend RTRW revision based on empirical evidence to optimize infrastructure investment allocation and support more equitable regional development. This research contributes theoretically by demonstrating the applicability of integrated spatial analysis methods to Indonesian regional contexts and provides practical policy guidance for responsive spatial planning in decentralized governance systems.